Pengaruh Pemanfaatan Kelas Elektronik Terhadap Efektifitas dan Efisiensi Proses Belajar STMIK XYZ - Dicky Pratama; Hendri Sopryadi (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2016)
Electronic classrooms at STMIK XYZ for this is believed to contribute to the learning process. Lecturers, students and all staff use the classroom to communicate remotely, disseminate knowledge, information capture and so forth. It is not yet known whether the use of electronic classrooms that can impact the efficiency and effectiveness of the learning process. This study aims to measure whether the use of electronic classrooms significantly influence the effectiveness and efficiency of the learning process. The method used is regression analysis to test the normality, linearity and homogeneity. The test results show that a variety of electronic classrooms affect the effectiveness and efficiency of the learning process